Prebreakup Arc Intensification due to Short Circuiting of Mesoscale Plasma Flows Over the Plasmapause. Issue 5 (9th May 2020) - Mishin, Evgeny; Streltsov, Anatoly
Abstract: The prebreakup arc at the inner edge of the auroral boundary is intensified upon arrival of an auroral streamer—the ionospheric signature of the earthbound mesoscale plasma flows (MPF). Yet the cause of electron precipitation enhancement only in this region remains unclear. We suggest that the intensified precipitation comes from the turbulent plasmasphere boundary layer (TPBL) that forms due to short circuiting of MPFs over the presubstorm plasmapause and overlaps with the plasma sheet (PS) inner boundary. Resonance interaction of the PS electrons with intense low‐frequency plasma waves leads to enhanced precipitation from this narrow region. Indeed, the DMSP spacecraft observations near the substorm onset show intensified electron fluxes in a narrow region near the auroral boundary, which maps into the TPBL. The same pattern observed in conjunction with postonset auroral streamers points to the common mechanism, which is the short‐circuiting process. Therefore, we suggest that the enhanced precipitation into the prebreakup arc is causally related to the MPFs' short circuiting over the plasmapause. Key Points: Short circuiting of mesoscale plasma flows over the plasmapause explains the prebreakup arc intensification DMSP observations reveal intensified electron precipitation localized near the substorm auroral boundary The same precipitation pattern during postonset auroral streamers points to the common, short‐circuiting mechanism